Analysis and Optimization of an Aftermarket Intercooler Spray‟s Nozzle - M.I.N, Ma'arof; Usman, Shahid; Girma, T. Chala; Sathurshan, Suresh (International Journal of Emerging Technology and Advanced Engineering, 2022)
Nowadays an intercooler is commonly integrated in vehicles to cool the air during induction. However, the intercooler does not perform effectively in countries where the climate is humid and hot as the air temperature is relatively higher. Therefore, this study is focused at developing an aftermarket intercooler spray to combat this predicament. The goal of the study was to improve the performance of a cooling-spray-integrated topmount intercooler via the analysis of nozzle diameter and spraying angles. Experiments were conducted on five nozzle types and three spraying angles: 00 , 150 and 300 . It was observed that the efficiency of the intercooler with the spray cooling unit was improved from 89.7% to 95.33%. A B1/8BX3 Hollow Cone Nozzle gave the highest efficiency, followed by B1/8QPPA+QPHA-5 Standard Full Cone Nozzle, HB1/8VV8007 Flat Fan Nozzle, HB1/8VV-6507 Flat Fan Nozzle and B1/8GG-4.3W Standard Full Cone Nozzle. The highest efficiency was observed at nozzle spray angle of 150 . Nozzle diameter and spraying angle were found critical in ensuring an enhanced overall performance of the intercooler.